Energy Modeling for NZEBs: A Case-study. (November 2015) - Micono, Carlo; Zanzottera, Guido
Abstract: The paper describes the dynamic energy modeling activity performed to achieve a n+NZEB (at the same time Net and Nearly Zero Energy Building), starting from the early design stage to the construction management. The modeling tool IES has been used to assist the strategy planner in the definition of the sustainability targets and the specialists in the detailed design of HVAC system, glazed façade and lighting equipment. Then, the energy model has been updated after every variation occurred during the construction phase and the results of the dynamic simulation have been checked to guarantee the energy performances forecasted. The paper emphasizes the choices taken in the energy model build-up, with a peculiar focus on simplifications applied. Also, the interactions between different assessment tools is discussed.